Head and neck cancer PEG site metastases: Association with PEG placement method. Issue 5 (7th January 2019) - Montes de Oca, Mary K.; Nye, Anthony; Porter, Caroline; Collins, Justin; Satterfield, Corey; Schammel, Christine M. G.; Trocha, Steven D.
Abstract: Background: Many patients with head and neck cancer (HNC) will require feeding tube placement for nutritional support using percutaneous endoscopic gastrostomy (PEG) tube. Rarely, HNC metastases have been reported at the PEG site, a morbidity associated with a poor outcome. Methods: Along with a case report, an evaluation of PEG placement methods with metastases from the literature was completed along with a statistical analysis of the literature to determine PEG site metastases and method of placement correlations. Results: The incidence of PEG metastases in patients with HNC with the "pull" method is statistically identical to that of patients receiving any other method for PEG placement. Conclusions: When considering options for the placement of PEG tubes in patients with HNC, the "pull" method should not be considered as a technique which will put patients at risk for PEG site metastases more than any other method of placement.